2019
DOI: 10.1093/ofid/ofz511
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Polymerase Chain Reaction Combined With Culture for the Diagnosis of Bone and Joint Infections: A Prospective Test Performance Study

Abstract: BackgroundThe microbiological diagnosis of bone and joint infections (BJI) currently relies on cultures, and the relevance of molecular methods is still debated. The aim of this study was to determine whether polymerase chain reaction (PCR) could improve the etiological diagnosis of BJI.MethodsA prospective study was conducted during a 4-year period at Lariboisiere University Hospital (Paris, France), including patients with suspicion of infectious spondylodiscitis, septic arthritis, prosthetic joint infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…By providing increased accuracy in pathogen detection, results of amplification-based, molecular assays may support this decision-making process by providing critical information on causative pathogens in addition to conventional culture-based techniques. In fact, a previous study has reported a higher sensitivity of culture in combination with PCR than that of culture alone to detect infection-causing organisms (95.5% vs 81.8%, (Jacquier et al, 2019). In line with previous reports (Bemer et al, 2014) our study provides evidence that 16S rDNA PCR approaches to culture-independent pathogen detection is of apparent low sensitivity, with an estimated sensitivity of 37.5% compared to SOC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By providing increased accuracy in pathogen detection, results of amplification-based, molecular assays may support this decision-making process by providing critical information on causative pathogens in addition to conventional culture-based techniques. In fact, a previous study has reported a higher sensitivity of culture in combination with PCR than that of culture alone to detect infection-causing organisms (95.5% vs 81.8%, (Jacquier et al, 2019). In line with previous reports (Bemer et al, 2014) our study provides evidence that 16S rDNA PCR approaches to culture-independent pathogen detection is of apparent low sensitivity, with an estimated sensitivity of 37.5% compared to SOC.…”
Section: Discussionsupporting
confidence: 88%
“…Use of a spPCR showed increased pathogen yield compared to a 16S rDNA PCR, and this was also true for the detection of staphylococci, having found to be specifically challenging for 16S rDNA PCR assays (Jacquier et al, 2019). Thus, spPCR might prove as a reasonable addition to culture-based pathogen detection strategies in BJI.…”
Section: Discussionmentioning
confidence: 97%
“…Focusing on the study design, neither orthopaedic nor else studies, which are comparing direct 16S-rRNAgene analysis and the difference in the microbiome distribution in different sampling modalities exist. Only a few studies have been investigating, whether using 16S-rRNA-gene analysis resulted in similar or even improved results, than normal microbiological testing [26,[44][45][46]. Due to this fact and the appropriate results of 16S-rRNA-gene analysis in microbiome analysis of the oral cavity, we assume, that this is a reliable tool for such investigation [30,32,34,47].…”
Section: Discussionmentioning
confidence: 99%
“…These include (i) the fact that they cannot be used to measure antimicrobial susceptibility, (ii) the introduction of bias through the use of general primers for 16 s rRNA sequencing that do not bind equally to all bacteria and (iii) the difficulty in identification beyond the genus due to high similarity among closely related species. Several studies have compared the use of culturing and amplicon sequencing for diagnostics, generally reporting a higher sensitivity for sequencing compared to culturing, especially in the investigation of chronic infections [62][63][64]. If sequencing is to replace culturing as a clinical diagnostic method, it must be standardized, automated and cost-efficient.…”
Section: Examination Methodsmentioning
confidence: 99%